Race effects on pathological and functional outcomes after robotic partial nephrectomy in a single academic tertiary care center. Issue 1 (March 2016) - Kara, Onder; Andrade, Hiury; Zargar, Homayoun; Akca, Oktay; Maurice, Matthew; Caputo, Peter; Ramirez, Daniel; Malkoc, Ercan; Modlin, Charles; Kaouk, Jihad
Abstract To explore the potential effects of race on pathological outcomes of renal tumor and on kidney function preservation in the patients undergoing robotic partial nephrectomy (RPN) at our center. Retrospective review of our institutional review board approved database for African-American (AA) patients undergoing RPN from 2006 to 2014 was performed. AA and non-AA groups were compared with regards to demographics, tumor characteristics, functional data and, oncological outcomes. For functional outcomes, groups were matched (1:1) in terms of age, preoperative estimated glomerular filtration rate (eGFR) and R.E.N.A.L score. From the total of 1005 patients, 84 were AA. Age and the tumor size were comparable between the two groups (2.7 vs. 3 cm;p  = 0.29). Proportion of patients with papillary RCC was higher among AAs compared to non-AAs (43.3 vs. 19.4 %;p  < 0.001). After matching AA patients with non-AA counterparts (1:1 matching), eGFR preservation at latest follow up after surgery was comparable between groups (84.3 vs. 85 %;p  = 0.25). AA race (OR 3.62, p  < 0.001), male gender (OR 2.05, p  < 0.001) and low preoperative eGFR (OR 0.97, p  < 0.001) were predictors of papillary RCC on multivariate analyses. The incidence of papillary RCC is higher in AA patients undergoing RPN. There was no difference in kidney function recovery after robotic partial nephrectomy in both AA and non-AA groups. AA race itself is not a significant factor in determining renal malignancy. Further studies are needed to clarify the impact of higher prevalence of papillary tumors in AA group in terms of long-term oncological and functional outcomes.